Communicating risk in active surveillance of localised prostate cancer: a protocol for a qualitative study. Issue 10 (5th October 2017) - Rapport, Frances; Hogden, Anne; Gurney, Howard; Gillatt, David; Bierbaum, Mia; Shih, Patti; Churruca, Kate
Abstract : Introduction: One in five men is likely to receive a diagnosis of prostate cancer (PCa) by the age of 85 years. Men diagnosed with low-risk PCa may be eligible for active surveillance (AS) to monitor their cancer to ensure that any changes are discovered and responded to in a timely way. Communication of risk in this context is more complicated than determining a numerical probability of risk, as patients wish to understand the implications of risk on their lives in concrete terms. Our study will examine how risk for PCa is perceived, experienced and communicated by patients using AS with their health professionals, and the implications for treatment and care. Methods and analysis: This is a proof of concept study, testing out a multimethod, qualitative approach to data collection in the context of PCa for the first time in Australia. It is being conducted from November 2016 to December 2017 in an Australian university hospital urology clinic. Participants are 10 men with a diagnosis of localised PCa, who are using an AS protocol, and 5 health professionals who work with this patient group (eg, urologists and Pca nurses). Data will be collected using observations of patient consultations with health professionals, patient questionnaires and interviews, and interviews with healthcare professionals. Analysis will be conducted in two stages. First, observational data from consultations will be analysed thematically to encapsulate various dimensions of risk classification and consultation dialogue. Second, interview data will be coded to derive meaning in text and analysed thematically. Overarching themes will represent patient and health professional perspectives of risk communication. Ethics and dissemination: Ethical approval for the study has been granted by Macquarie University Human Research Ethics Committee, approval 5201600638. Knowledge translation will be achieved through publications, reports and conference presentations to patients, families, clinicians and researchers.